Forms of self-knowledge in the Platonic Republic - Gutiérrez, Raúl (Estudios de Filosofía, 2008)
Recent research on the Republic has brought to the table an issue that until now had not been considered as part of the variety of those examined in that dialogue. Obviously I am referring to the issue of self-knowledge. And this has occurred in two complementary directions. On the one hand, based on the consideration of a widely neglected passage of the allegory of the cave, and, on the other, insofar as the relationship of the rational soul with the Idea of ​​Good is seen as the possibility of a solution to the Charmides aporias on reflective knowledge. In any case, one of the conclusions of these studies is that the subject of knowledge or ignorance of oneself alluded to in the allegory of the cave does not constitute an isolated reason and is not left aside, but precisely that knowledge reaches its full realization in the knowledge of the Idea of ​​Good. [Fragment]